Some Reverse Inequalities on Hyperinner Product Spaces - Taghavi, Ali; Darvish, Vahid; Nazari, Haji Mohammad (Eurasian Mathematical Journal, 2017)
In this paper, by applying a new definition of a hyperinner product, we establish some reverse Schwarz inequalities on hyperinner product spaces over the real or complex fields which also gives some interesting reverse Schwarz inequalities in the classic inner product spaces.